circ_0101802 functions as a sponge of miR-1236-3p to facilitate the proliferation, migration and invasion of colorectal cancer via regulating MACC1 - Liang Bai; Zhifeng Gao; An Jiang; Song Ren; Baotai Wang (Elsevier, 2021)
Circular RNAs (circRNAs) have been shown to be involved in the progression of many diseases, including cancer. However, the role of circ_0101802 in the proliferation, migration and invasion of colorectal cancer (CRC) has not been studied. Our results showed that circ_0101802 was highly expressed in CRC tumor tissues and cells. Functional experiments suggested that circ_0101802 knockdown could inhibit the proliferation, migration and invasion of CRC cells in vitro and CRC tumorigenesis in vivo. In the terms of mechanism, we discovered that circ_0101802 could act as a sponge of miR-1236-3p, and miR-1236-3p could target MACC1. The rescue experiments revealed that miR-1236-3p inhibitor could reverse the inhibition effect of circ_0101802 silencing on CRC proliferation, migration and invasion, and MACC1 overexpression also could abolish the negative regulation of miR-1236-3p on CRC proliferation, migration and invasion. More important, our data confirmed that circ_0101802 sponged miR-1236-3p to positively regulate MACC1. In summary, our results revealed that circ_0101802 functioned as a tumor promoter in CRC, which could facilitate CRC proliferation, migration and invasion via regulating the miR-1236-3p/MACC1 axis.